MEMBANGUN KREATIVITAS MAHASISWA MELALUI PENERAPAN PROJECT BASED LEARNING DALAM MENGAJAR MATA KULIAH DRAMATURGI - Dewa Made, Agustawan (Suluh Pendidikan : Jurnal Ilmu-Ilmu Pendidikan, 2025)
The Dramaturgy course requires a learning approach that enhance students’ creativity, critical thinking, and collaborative skills. This research aims to explore the implementation of the Project-Based Learning (PjBL) model in the Dramaturgy course. The research employs a qualitative descriptive method with a case study approach in the Performing Arts Education study program. The findings shows that PjBL enhances student engagement in the learning process, cultivates analytical skills in interpreting dramatic texts, and improves understanding of the structure and elements of dramaturgy. Project-Based Learning (PjBL) also provides students with hands-on experience in developing performance projects based on texts. Therefore, PjBL is an effective learning strategy for teaching Dramaturgy in higher education.